Regulation of the gender dimensions of public services of regional hub countries: problems and shortcomings. (Journal of Economic Research & Business Administration, 2016)
Studying the gender dimension in some countries, including the countries of the regional hub should be noted that there are problems and disadvantages of the regulation of gender aspects in the public service. This article discusses the difficulty of involving women in power, as well as excerpts from the main international instruments in the field of women’s rights. In this article, we would consider the gender dimensions of regulation of public services ability to make some of the regional hub. Measures to regulate the problems and the lack of gender aspects of public services of a regional hub. The author carried out a comparative analysis of the gender dimension of public service of the regional hub. The questions relating to the protection of women’s interests in public administration as well as the participation of women in politics and decision-making level in the public service.
Keywords: gender; gender inequality; public administration; politics; the country’s regional hub; problems and shortcomings of the regulation of gender aspects of public services; public service.